Influence of Entrepreneurial Psychology and Spirit on the Cultivation of Students’ Entrepreneurial Values and Ability Under the New Media - Li, Ping; Chen, Xiaozhou (Frontiers in Psychology, 2021)
This paper studies the influence of entrepreneurial spirit on college students' entrepreneurial ability and entrepreneurial values. Firstly, the impact of entrepreneurial psychology and entrepreneurial spirit on entrepreneurial values is analyzed. Secondly, the role of entrepreneurial values in Innovation and Entrepreneurship Education (IEE) is analyzed and summarized under new media. Then, based on entrepreneurial psychology and entrepreneurial spirit, a Questionnaire Survey (QS) is designed to investigate the entrepreneurial values of students in one university in Shaanxi Province, China. The QS analysis suggests that most respondents hold a positive attitude, and their attitude is on the rise. The QS results of "Reasons for entrepreneurial failure" show that 40.37%, 31.9%, 25.98%, and 11.75% of respondents think they lack financial support, business skills, ability, and understanding of policies and laws, respectively. The QS results of "What factors influence entrepreneurial values?" reveal that 39.43% of the respondents chose the "Models of successful entrepreneurs", successful entrepreneur models can effectively encourage students to receive IEE, followed by 28.94% who choose "Achieve their own life goals". In terms of "Solutions against entrepreneurial risks", nearly 70% of the students have chosen the negative options. In terms of "Which is the most important entrepreneurial quality?", more students choose entrepreneurial values rather than entrepreneurial quality, proving that students generally lack entrepreneurial values. Given these problems, corresponding countermeasures are put forward to strengthen entrepreneurial psychology and IEE, in an attempt to cultivate college students' entrepreneurial values and entrepreneurial ability under the new media. The results provide some data support for the impact of college students' entrepreneurial values and entrepreneurial ability.